Fine‐scale spatial genetic structure of the black truffle (Tuber melanosporum) investigated with neutral microsatellites and functional mating type genes. Issue 1 (10th April 2013) - Murat, Claude; Rubini, Andrea; Riccioni, Claudia; De, Herminia; Akroume, Emila; Belfiori, Beatrice; Guaragno, Marco; Le, François; Robin, Christophe; Halkett, Fabien; Martin, Francis; Paolocci, Francesco
Summary The genetic structure of ectomycorrhizal (ECM) fungal populations results from both vegetative and sexual propagation. In this study, we have analysed the spatial genetic structure of Tuber melanosporum populations, a heterothallic ascomycete that produces edible fruit bodies. Ectomycorrhizas from oaks and hazels from two orchards were mapped and genotyped using simple sequence repeat markers and the mating type locus. The distribution of the two T. melanosporum mating types was also monitored in the soil. In one orchard, the genetic profiles of the ascocarps were compared with those of the underlying mycorrhizas. A pronounced spatial genetic structure was found. The maximum genet sizes were 2.35 and 4.70 m in the two orchards, with most manifesting a size < 1 m. Few genets persisted throughout two seasons. A nonrandom distribution pattern of the T. melanosporum was observed, resulting in field patches colonized by genets that shared the same mating types. Our findings suggest that competition occurs between genets and provide basic information on T. melanosporum propagation patterns that are relevant for the management of productive truffle orchards.